Transforming conflict with an economic dividend: The Sri Lankan experience - Saman Kelegama (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Peace can generate an economic dividend, which can be further increased by appropriate economic reform. This dividend can in turn be used to raise popular support for conflict resolution measures along the road to achieving a final political settlement, a strategy that characterizes the recent period in Sri Lanka. However, despite an increase in economic growth following the cessation of hostilities between the Liberation Tigers of Tamil Eelam (LTTE) and the government, no substantial dividend materialized for either government supporters in the South or LTTE supporters in the war-torn Northeast. The causes of this failure include delays in disbursing aid which would have eased adjustment to economic reforms—resulting in cuts to public spending that affected Southern households—and weak institutions that impeded the effective use of aid in the Northeast. The Sri Lankan experience highlights some important lessons for both government and donors on making use of an economic lever for consolidating a peace process and conflict resolution. It also highlights some of the dangers in relying too much on economic levers to consolidate a peace process when levels of mistrust are very high.
Keywords: H56; F33; O21; O53; 330; Sri Lanka; conflict resolution; economic dividend; foreign aid; Innere Sicherheit; Anpassungsprogramm des IWF; Entwicklung; Sri Lanka